2022
DOI: 10.25122/jml-2021-0154
|View full text |Cite
|
Sign up to set email alerts
|

Fimasartan ameliorates renal ischemia reperfusion injury via modulation of oxidative stress, inflammatory and apoptotic cascades in a rat model

Abstract: Ischemia-reperfusion injury (IRI) can be defined as changes in the functions and structures of the tissues resulting from the restoration of blood after a period of ischemia. This study aimed to assess the potential protective effect of Fimasartan (angiotensin receptor antagonist) in the bilateral renal IRI in male rats through its potential effect on renal functions, modulation of the inflammatory cascade, oxidative stress, and apoptotic effect. The animals were equally assigned into four groups. The sham (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…This finding was also reported in other research who found that rats exposed to renal ischemia reperfusion by occluding the renal pedicles for 30 min and restoring blood for 2h had higher caspase 3 and lower Bcl2 levels than the sham group. 26 Moexipril pretreatment group had a substantial reduction in caspase-3 kidney level and increased Bcl-2 compared to induced group (Figures 7 and 8). Thus, moexipril has antiapoptotic effects, although there is no previous study on Bcl-2 or caspase-3 in RIRI models.…”
Section: Discussionmentioning
confidence: 86%
“…This finding was also reported in other research who found that rats exposed to renal ischemia reperfusion by occluding the renal pedicles for 30 min and restoring blood for 2h had higher caspase 3 and lower Bcl2 levels than the sham group. 26 Moexipril pretreatment group had a substantial reduction in caspase-3 kidney level and increased Bcl-2 compared to induced group (Figures 7 and 8). Thus, moexipril has antiapoptotic effects, although there is no previous study on Bcl-2 or caspase-3 in RIRI models.…”
Section: Discussionmentioning
confidence: 86%
“…Not surprisingly, angiotensin II increases oxygen consumption by renal mitochondria [134]. While angiotensin receptor blockers (ARBs) have repeatedly shown benefits in animal models of AKI [135][136][137][138] and CKD in humans [139][140][141], the results from clinical trials of AKI with ARBs and angiotensin converting enzyme inhibitors (ACEIs) have had mixed results (Table 1). One potential adverse impact of ACEIs and ARBs in the setting of AKI is that they could worsen renal hypoperfusion.…”
Section: Angiotensin II Inhibitorsmentioning
confidence: 99%
“…Current studies have proposed dialysis treatment [23], alternative therapy [24], stem cell therapy [25][26][27], etc., but these treatments all have certain limitations. Based on this, more and more research is targeting the drug treatment of AKI [28][29][30].…”
Section: Introductionmentioning
confidence: 99%